Comparative Transcriptome Analysis of Salt Stress-Induced Leaf Senescence in Medicago truncatula - Dong, Shuwei; Sang, Lijun; Xie, Hongli; Chai, Maofeng; Wang, Zeng-Yu (Frontiers in Plant Science, 2021)
Leaves are the most critical portion of forage crops such as alfalfa (Medicago sativa). Leaf senescence caused by environmental stresses significantly impacts the biomass and quality of forages. To understand the molecular mechanisms and identify the key regulator of the salt stress-induced leaf senescence process, we conducted a simple and effective salt stress-induced leaf senescence assay in Medicago truncatula, which was followed by RNA-Seq analysis coupled with physiological and biochemical characterization. By comparing the observed expression data with that derived from dark-induced leaf senescence at different time points, we identified 3,001, 3,787, and 4,419 senescence-associated genes (SAGs) for salt stress-induced leaf senescence on day 2, 4, and 6, respectively. There were 1546 SAGs shared by dark and salt stress treatment across the three time points. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses showed that the 1546 SAGs were mainly related to protein and amino acids metabolism, photosynthesis, chlorophyll metabolism, and hormone signaling during leaf senescence. Strikingly, many different transcription factors (TFs) families out of the 1546 SAGs, including NAC, bHLH, MYB, and ERF, were associated with salt stress-induced leaf senescence processes. Using the transient expression system in Nicotiana benthamiana, we verified that three functional NAC TF genes from the 1546 SAGs were related to leaf senescence. These results clarify SAGs under salt stress in M. truncatula and provide new insights and additional genetic resources for further forage crop breeding.